New Plants for Florida: Turfgrass - Ken Quesenberry; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
There are more than four million acres of managed turfgrass in Florida, with 75 percent of these in residential lawns. Several warm-season turf species are important for use in Florida. The decision of which turfgrass species to use is based on the desired maintenance effort and geographic location within the state. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.